The complex case of Ceratitis cosyra (Diptera: Tephritidae) and relatives. A DNA barcoding perspective. (22nd February 2017) - Virgilio, M.; Manrakhan, A.; Delatte, H.; Daneel, J‐H.; Mwatawala, M. W.; Meganck, K.; Barr, N. B.; De Meyer, M.
Abstract: The mango fruit fly, Ceratitis ( Ceratalaspis ) cosyra, is a major agricultural pest affecting mango production in sub‐Saharan Africa. Morphological differences between C. cosyra and five closely related Ceratitis ( Ceratalaspis ) species ( C. discussa, C. pallidula, C. quinaria, C. silvestrii, C. striatella ) are subtle, so that their identification often requires specialized expertise. A previous study based on nuclear molecular markers (microsatellites) showed cryptic genetic variation within C. cosyra with separate microsatellite genotypic clusters also occurring in sympatry. This study aimed at verifying whether DNA barcoding can (a) separate C. cosyra from morphologically similar Ceratitis ( Ceratalaspis ) species and (b) resolve the cryptic genetic variation previously observed within C. cosyra . A subset of 62 C. cosyra specimens previously genotyped at 16 microsatellite loci was subjected to DNA barcoding. This data set was integrated with 130 DNA barcodes of C. cosyra, C. discussa, C. quinaria, C. silvestrii and C. striatella . Neighbor Joining, maximum likelihood and Bayesian tree reconstructions confirmed the presence of two main C. cosyra genotypic groups and resolved well‐supported groups corresponding to C. discussa, C. pallidula, C. striatella and to C. quinaria / C. silvestrii . The analysis of morphological characters did not show consistent morphological differences between the two groups of C. cosyra and called into question the morphological characters currently implemented in the identification of C. striatella . These results further support the hypothesis of cryptic speciation within the mango fruit fly and suggest that DNA barcoding represents a suitable complementary tool for the problematic diagnosis of C. cosyra and C. striatella .